PERAN KEPALA MADRASAH DALAM MEMBERDAYAKAN KELOMPOK DAN TIM - Makmur Syukri; Rambe, Nurmarito (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
At this time, the role of madrasa heads in empowering existing human resources in educational institutions is said to be sufficient or fulfilled. Several roles of madrasa heads in leading, however, there are still many madrasa heads and existing resources in educational institutions that the importance of implementing self-management means all the steps and the act of organizing, managing oneself. Apart from that, self-management can also mean managing all elements of personal potential, controlling the ability to achieve good things, such as in a group or team. A group is a group of individuals who interact and communicate with each other. Teams and groups have differences in terms of understanding, types, characteristics and process of formation. Teams tend to be more effective, productive and qualified than groups in completing certain tasks or projects. This research is literary in nature, including the type of library research. Library research is research in which data collection is carried out by collecting data from various literature. The literature studied is not limited to books but can also take the form of materials, journals and other research. The emphasis of library research is to find various theories, laws, propositions, principles, opinions, ideas and so on that can be used to analyze and solve the problems being studied. The results of this research show the importance of implementing self-management in groups and teams. So the school/madrasah principal is responsible for organizing educational activities, school administration, developing teaching and education staff, and utilizing and maintaining school facilities and infrastructure. With close cooperation and various parties in society, everyone will feel responsible for the success of the educational institution.